Laminated organic light-emitting device and application thereof

By designing a gradient-doped first connecting layer in the stacked organic electroluminescent device, the problems of high driving voltage, low luminous efficiency and short life in the prior art are solved, and the effects of low driving voltage, high efficiency and long life are achieved.

CN119767943APending Publication Date: 2025-04-04FOSHAN ELECTRICAL & LIGHTING

Patent Information

Application Number
CN202411801483.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing stacked organic electroluminescent devices have problems such as high driving voltage, low luminescence efficiency and short life.

Method used

A laminated organic electroluminescent device is designed, which includes an anode layer arranged in sequence from bottom to top, at least two light emitting units, a cathode layer, and a connecting layer for connecting two adjacent light emitting units. The connecting layer consists of a first connecting layer and a second connecting layer, the first connecting layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material gradually decreases from one side of the second connecting layer to the light emitting unit side.

Benefits of technology

Through the gradient-doped first connection layer structure, the energy level barrier is effectively eliminated, the driving voltage drop is reduced, the carrier generation ability is improved, and the exciton quenching effect of n-type dopants on the luminescent unit is avoided, thereby achieving the characteristics of low driving voltage, high efficiency and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767943A_ABST
    Figure CN119767943A_ABST
Patent Text Reader

Abstract

The invention relates to the field of organic light-emitting devices, and particularly discloses a laminated organic light-emitting device and application thereof. The laminated organic light-emitting device comprises an anode layer, at least two light-emitting units, a cathode layer and a connecting layer used for connecting two adjacent light-emitting units which are sequentially arranged from bottom to top, the connecting layer comprises a first connecting layer and a second connecting layer which are sequentially arranged from bottom to top; the first connecting layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the first connecting layer is gradually reduced from one side of the second connecting layer to one side of the light-emitting unit; the second connection layer is composed of a p-type dopant material and an organic hole transport material. The connecting layer provided by the invention has stronger carrier generation capability and lower driving voltage drop, and can effectively avoid the exciton quenching effect of the dopant on the light-emitting unit, so that the laminated organic light-emitting device has the characteristics of low driving voltage, high efficiency and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electroluminescence, and in particular to a stacked organic electroluminescent device and its application. Background Art

[0002] Organic light-emitting diodes (OLEDs) technology is currently widely used in small and medium-sized display products such as smartphones and wearable devices. Furthermore, OLED lighting devices that combine single-color or multi-color (three primary colors or complementary two-color) luminescent materials can also be used in indoor (outdoor) lighting, automotive lighting and other fields. OLED lighting devices have put forward more stringent requirements on the light output efficiency, aging life, operating temperature and other indicators of luminescent materials, and the device structure and its preparation process often play a decisive role in the performance of luminescent materials.

[0003] OLED lighting products usually need to have high brightness, low driving voltage and long working life performance. For this reason, a connection layer (charge generation layer, CGL) structure is needed to connect multiple light-emitting units in series to obtain a stacked OLED device. Compared with a single light-emitting unit device, the luminous brightness of the stacked device under the same current drive will increase exponentially, and a longer device life will be obtained. In order to obtain high-performance stacked OLED devices, the following two technical difficulties need to be solved for the connection layer unit: 1) In order to obtain a low driving voltage, it is necessary to solve the energy level mismatch problem of the connection layer heterojunction, thereby reducing the driving voltage drop on the connection layer unit; 2) The stacked OLED device needs to achieve a doubling effect of luminous efficiency. Therefore, each light-emitting unit needs to maintain a high-performance luminous efficiency consistent with a single light-emitting unit device, which requires the connection layer to achieve efficient generation of carriers and transport them to the light-emitting unit, so that the carriers in the device light-emitting layer can efficiently recombine and emit light. Therefore, it is urgent to develop new connection layer materials and device structures with low driving voltage and excellent luminous performance.

[0004] Academic researchers and panel manufacturers have conducted relevant research on solving the technical problems of the connection layer. For example, in patent application CN114520301A, a stacked organic light-emitting device is disclosed, in which a spacer layer structure is introduced between the n-type doping layer and the p-type doping layer to prevent the n-type dopant from easily diffusing into the p-type doping layer and the adjacent light-emitting layer, thereby causing the device driving voltage to rise. On the other hand, patent application CN116583133A proposes an alternating interface modification layer structure for reducing the injection barrier of carrier injection into the first connection layer and the second connection layer, thereby reducing the driving voltage drop of the stacked device at the connection layer, so that the stacked organic electroluminescent device has the characteristics of low driving voltage and high efficiency. Although the above-mentioned connection layer structure scheme can solve the energy level mismatch problem of the heterojunction, its preparation process is complicated, and there is still a voltage drop at the alternating interface.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a stacked organic electroluminescent device and its application, aiming to solve the problems of high driving voltage, low luminous efficiency and short life of the existing stacked organic electroluminescent devices.

[0007] In order to solve the above technical problems, the present invention provides a stacked organic electroluminescent device in a first aspect, characterized in that it comprises: an anode layer, at least two light-emitting units, a cathode layer, and a connecting layer for connecting two adjacent light-emitting units arranged in sequence from bottom to top; the connecting layer comprises a first connecting layer and a second connecting layer arranged in sequence from bottom to top;

[0008] The first connection layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the first connection layer gradually decreases from the second connection layer side to the light-emitting unit side;

[0009] The second connection layer is composed of a p-type dopant material and an organic hole transport material.

[0010] As an improvement of the above technical solution, the doping concentration of the n-type dopant material of the first connecting layer decreases in a linear decreasing manner from the second connecting layer side to the light emitting unit side.

[0011] As an improvement of the above technical solution, the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the second connecting layer is 5 mass% to 15 mass%, and the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the light-emitting unit is 0.5 mass% to 5 mass%.

[0012] As an improvement of the above technical solution, the doping concentration of the n-type dopant material of the first connecting layer decreases in a gradient manner from the second connecting layer side to the light-emitting unit side, and the set concentration gradient number is an integer greater than or equal to 3.

[0013] As an improvement of the above technical solution, the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the second connecting layer is 5 mass% to 15 mass%, and the doping concentration range of the n-type dopant material on the side of the first connecting layer close to the light-emitting unit is 0.5 mass% to 5 mass%.

[0014] As an improvement of the above technical solution, the thickness of the first connecting layer is 20nm to 100nm;

[0015] The thickness of the second connection layer is 20 nm to 300 nm.

[0016] As an improvement of the above technical solution, the n-type dopant material is selected from at least one of lithium, cesium, magnesium, gold, silver, copper, zinc, ytterbium, molybdenum trioxide, cesium carbonate, and lithium carbonate.

[0017] As an improvement of the above technical solution, the organic electron transport materials are all made of nitrogen heterocyclic units, and the nitrogen heterocyclic units are selected from at least one of compounds N-1 to compounds N-28:

[0018]

[0019]

[0020] As an improvement of the above technical solution, the p-type dopant material of the second connecting layer is a deep LUMO energy level material, and the deep LUMO energy level material is selected from MoO 3 , WO 3 、V 2 O 5 、MoO 2 、Co 3 O 4 and at least one of the following compounds HI-1 to HI-18:

[0021]

[0022]

[0023] The second aspect of the present invention further provides an application of the stacked organic electroluminescent device, wherein the stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.

[0024] The implementation of the present invention has the following beneficial effects:

[0025] In the stacked organic electroluminescent device in one embodiment of the present invention, a connecting layer is arranged between two adjacent light-emitting units, which includes a first connecting layer and a second connecting layer arranged in sequence from bottom to top, the first connecting layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the first connecting layer gradually decreases from the second connecting layer side to the light-emitting unit side; this gradient doped first connecting layer structure can not only effectively eliminate the energy level barrier between the first connecting layer and the second connecting layer, so that the overall connecting layer has a stronger carrier generation ability and a lower driving voltage drop, but also effectively avoid the quenching effect of a higher n-type dopant concentration on the excitons in the light-emitting unit, improve the luminous efficiency of the stacked device, and make the stacked organic electroluminescent device of the present invention have the characteristics of low driving voltage, high efficiency and long life. On the other hand, since the connecting layer only includes the first connecting layer and the second connecting layer, it has the characteristics of simple structure but excellent performance of the connecting layer, which is conducive to simplifying the preparation process and is worthy of commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic structural diagram of a stacked organic electroluminescent device in one embodiment of the present invention;

[0027] Figure 2 is a schematic structural diagram of a stacked organic electroluminescent device in another embodiment of the present invention;

[0028] Figure 3 is a schematic structural diagram of a stacked organic electroluminescent device in another embodiment of the present invention;

[0029] Reference numerals:

[0030] 100, anode layer, 200, first light-emitting unit, 210, first hole transport layer, 220, first electron blocking layer, 230, first light-emitting layer, 240, first hole blocking layer, 250, first electron transport layer, 300, connecting layer, 310, first connecting layer, 320, second connecting layer, 400, second light-emitting unit, 410, second hole transport layer, 420, second electron blocking layer, 430, second light-emitting layer, 440, second hole blocking layer, 450, second electron transport layer, 500, cathode layer, 600, hole injection layer, 700, electron injection layer, 800, third light-emitting unit, 900, fourth light-emitting unit. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail with specific embodiments below. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be understood that, under the premise of no conflict, any and all embodiments of the present invention can be combined with the technical features in any other embodiment or multiple other embodiments to obtain another embodiment. The present invention includes such a combination to obtain another embodiment.

[0033] In this specification, groups and substituents thereof can be selected by those skilled in the art to provide stable structural moieties and compounds. When substituents are described by conventional chemical formulas written from left to right, the substituents also include chemically equivalent substituents obtained when the structural formula is written from right to left.

[0034] The section headings used in this specification are only for the purpose of organizing the article and should not be interpreted as limiting the subject matter described. All documents or portions of documents cited in this invention, including but not limited to patents, patent applications, articles, books, manuals and papers, are incorporated herein by reference in their entirety.

[0035] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.

[0036] It should be understood that the singular forms used in the present invention, such as "a", include plural references unless otherwise specified. In addition, the term "comprising" is an open limitation and not a closed one, that is, it includes the contents specified in the present invention, but does not exclude other aspects.

[0037] See also Figure 1In a first aspect, the present invention provides a stacked organic electroluminescent device, which includes an anode layer 100, at least two light-emitting units, a cathode layer 500, and a connection layer 300 for connecting two adjacent light-emitting units, which are arranged in sequence from bottom to top; the connection layer 300 includes a first connection layer 310 and a second connection layer 320, which are arranged in sequence from bottom to top. The first connection layer 310 is made of an n-type dopant material and an organic electron transport material, the second connection layer 320 is composed of a p-type dopant material and an organic hole transport material, and the doping concentration of the n-type dopant material of the first connection layer 310 gradually decreases from the second connection layer 320 side to the light-emitting unit side; the gradient-doped first connection layer 310 structure can effectively eliminate the energy level barrier between the first connection layer 310 and the second connection layer 320, so that the connection layer 300 has a stronger carrier generation capability and a lower driving voltage drop, and effectively avoids the exciton quenching effect of the dopant on the light-emitting unit, thereby improving the luminous efficiency and device life of the stacked organic electroluminescent device.

[0038] Furthermore, in one embodiment, the stacked organic electroluminescent device includes two light-emitting units, namely a first light-emitting unit 200 and a second light-emitting unit 400, wherein the first light-emitting unit 200 is disposed between the first connection layer 310 and the anode layer 100, and the second light-emitting unit 400 is disposed between the second connection layer 320 and the cathode layer 500, wherein the first light-emitting unit 200 includes a first light-emitting layer 230, and the second light-emitting unit 400 includes a second light-emitting layer 430. The doping concentration of the n-type dopant material of the first connection layer 310 gradually decreases from the second connection layer 320 side to the first light-emitting layer 230 side.

[0039] In some specific and preferred embodiments, the doping concentration of the n-type dopant material of the first connection layer 310 decreases from the second connection layer 320 side to the first light-emitting layer 230 side in a linear decreasing manner. The doping concentration of the n-type dopant material is reduced in a linear decreasing manner, which can reduce the LUMO electron injection energy level barrier between the first connection layer 310 and the second connection layer 320, so that electrons can enter the first connection layer 310 from the second connection layer 320 without an injection barrier. At this time, the doping concentration of the n-type dopant material on the side of the first connection layer 310 close to the second connection layer 320 is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connection layer 310 close to the first light-emitting layer 230 is in the range of 0.5 mass % to 5 mass %.

[0040] Alternatively, the doping concentration of the n-type dopant material of the first connection layer 310 is gradually decreased from the second connection layer 320 side to the first light-emitting layer 230 side in a gradient decreasing manner. Compared with the linear decreasing manner of the doping concentration, the gradient decreasing manner can reduce the difficulty of the preparation process. The number of concentration gradients set is an integer greater than or equal to 3, preferably 3 to 6. If the number of concentration gradients is set too much, it will increase the difficulty of the process and is not conducive to simplifying the preparation process. At this time, the doping concentration range of the n-type dopant material on the side of the first connection layer 310 close to the second connection layer 320 is 5 mass% to 15 mass%, and the doping concentration range of the n-type dopant material on the side of the first connection layer 310 close to the first light-emitting layer 230 is 0.5 mass% to 5 mass%.

[0041] Preferably, the thickness of the first connection layer 310 is 20 nm to 100 nm, and is exemplarily 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm or 95 nm, but is not limited thereto.

[0042] Optionally, the n-type dopant material in the first connection layer 310 is selected from at least one of lithium, cesium, magnesium, gold, silver, copper, zinc, ytterbium, molybdenum trioxide, cesium carbonate, and lithium carbonate. The organic electron transport material is composed of a nitrogen heterocyclic unit, and the nitrogen heterocyclic unit is selected from at least one of compounds N-1 to N-28, and its specific structure is as follows:

[0043]

[0044]

[0045]

[0046] Optionally, the second connection layer 320 is made of a p-type dopant material and an organic hole transport material, wherein the p-type dopant material is a deep LUMO energy level material, and the deep LUMO energy level material is selected from MoO 3 , WO 3 、V 2 O 5 、MoO 2 、Co 3 O 4 and at least one of the following compounds HI-1 to HI-18: The organic hole transport material is described in detail later.

[0047]

[0048]

[0049] Preferably, in one implementation, the thickness of the second connection layer 320 is 20 nm to 300 nm, illustratively 40 nm, 70 nm, 100 nm, 130 nm, 160 nm, 190 nm, 210 nm, 240 nm, 270 nm or 290 nm, but is not limited thereto.

[0050] Specifically, the light-emitting unit in the present invention may be a single-layer, double-layer or multi-layer OLED device structure commonly used in the art, but is not limited thereto. For example, in one embodiment, see Figure 1 The stacked organic electroluminescent device includes an anode layer 100, a hole injection layer 600, a first light-emitting unit 200, a first connection layer 310, a second connection layer 320, a second light-emitting unit 400, an electron injection layer 700 and a cathode layer 500 arranged in sequence from bottom to top. The first light-emitting unit 200 includes a first hole transport layer 210, a first electron blocking layer 220, a first light-emitting layer 230, a first hole blocking layer 240 and a first electron transport layer 250 arranged in sequence from bottom to top; the second light-emitting unit 400 includes a second hole transport layer 410, a second electron blocking layer 420, a second light-emitting layer 430, a second hole blocking layer 440 and a second electron transport layer 450 arranged in sequence from bottom to top.

[0051] For example, in another embodiment, see Figure 2 The stacked organic electroluminescent device may include an anode layer 100, a first light-emitting unit 200, a first connection layer 310, a second connection layer 320, a second light-emitting unit 400 and a cathode layer 500 arranged in sequence from bottom to top. The first light-emitting unit 200 includes a first hole transport layer 210, a first light-emitting layer 230 and a first electron transport layer 250 arranged in sequence from bottom to top; the second light-emitting unit 400 includes a second hole transport layer 410, a second light-emitting layer 430 and a second electron transport layer 450 arranged in sequence from bottom to top.

[0052] It should be noted that the stacked organic electroluminescent device in the present invention may include a plurality of light-emitting units, illustratively including 3 light-emitting units, 4 light-emitting units or 6 light-emitting units, but not limited thereto. Figure 3 In one embodiment, the stacked organic electroluminescent device includes four light-emitting units, namely a first light-emitting unit 200, a second light-emitting unit 400, a third light-emitting unit 800 and a fourth light-emitting unit 900, and a connecting layer 300 is provided between any two light-emitting units. The specific structural compositions of the four light-emitting units may be the same or different.

[0053] Furthermore, in order to improve the luminous efficiency of the stacked organic electroluminescent device, see Figure 1 , Figure 3In one embodiment, a hole injection layer 600 is provided between the anode layer 100 and the light-emitting unit closest to the anode layer 100 , and an electron injection layer 700 is provided between the cathode layer 500 and the light-emitting unit closest to the cathode layer 500 .

[0054] Specifically, the hole injection layer 600 can promote the injection of holes into the light-emitting unit, reduce the driving voltage of the organic electroluminescent device, and improve the luminous efficiency and device life. The film thickness of the hole injection layer 600 is not particularly limited, and is preferably 1nm to 150nm. Furthermore, the hole injection layer 600 is made of an organic hole transport material, but is not limited thereto. The organic hole transport material is an aromatic amine compound, and the aromatic amine compound is one or more of the following formulas (I) and (II);

[0055]

[0056] In formula (I) and formula (II),

[0057] Ar 1 ~Ar 4 It is a substituted or unsubstituted aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted fused aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 5 to 50 ring atoms, or a substituted or unsubstituted fused aromatic heterocyclic group having 5 to 50 ring atoms, or a group in which the above aromatic hydrocarbon group or fused aromatic hydrocarbon group is bonded to an aromatic heterocyclic group or fused aromatic heterocyclic group. In Ar 1 with Ar 2 Between, in Ar 3 with Ar 4 A ring can be formed between them.

[0058] Furthermore, the number of ring carbon atoms in the aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 12; the number of ring carbon atoms in the condensed aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 12; the number of ring carbon atoms in the aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and even more preferably 5 to 12; the number of ring carbon atoms in the condensed aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and even more preferably 5 to 12.

[0059] L is a substituted or unsubstituted aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted condensed aromatic hydrocarbon group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 5 to 50 ring atoms, or a substituted or unsubstituted condensed aromatic heterocyclic group having 5 to 50 ring atoms.

[0060] Furthermore, the number of ring carbon atoms in the aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 12; the number of ring carbon atoms in the condensed aromatic hydrocarbon group is preferably 6 to 30, more preferably 6 to 20, and even more preferably 6 to 12; the number of ring carbon atoms in the aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and even more preferably 5 to 12; the number of ring carbon atoms in the condensed aromatic heterocyclic group is preferably 5 to 30, more preferably 5 to 20, and even more preferably 5 to 12.

[0061] In some specific and preferred embodiments, the aromatic amine compound includes but is not limited to the following compounds HT-1 to HT-62.

[0062]

[0063]

[0064]

[0065]

[0066]

[0067]

[0068] Furthermore, the material of the hole injection layer 600 also includes a p-type dopant material containing a deep LUMO energy level. The doping concentration of the p-type dopant material is preferably 1 mass % to 10 mass %. The p-type dopant material is preferably one or more of the above compounds HI-1 to HI-18.

[0069] Specifically, the first hole transport layer 210 and the second hole transport layer 410 can allow holes to be transported therein in the form of jumping motion, making it easier for holes to be injected into the first light-emitting layer 230 and the second light-emitting layer 430, thereby achieving composite luminescence and improving luminous efficiency. The first hole transport layer 210 and the second hole transport layer 410 can both be a single-layer structure or a stacked structure. The first hole transport layer 210 and the second hole transport layer 410 are both made of organic hole transport materials, and the organic hole transport materials are specifically as described above. It should be noted that the organic hole transport materials of the first hole transport layer 210 and the second hole transport layer 410 can be the same substance or different substances.

[0070] Specifically, the thickness of the first hole transport layer 210 and the second hole transport layer 410 is not particularly limited, but is preferably 15 nm to 50 nm.

[0071] Specifically, the first electron blocking layer 220 and the second electron blocking layer 420 can block electrons from the light-emitting layer from entering the hole transport layer, and confine the electrons in the first light-emitting layer 230 and the second light-emitting layer 430, thereby improving the luminous efficiency. Specifically, the first electron blocking layer 220 and the second electron blocking layer 420 can be made of organic hole transport materials, and illustratively, the organic hole transport materials are triarylamine materials (such as NPB, TAPC, mCP, etc.), carbazole materials (such as TCTA, PCZAC, CCP, etc.), spirocyclic materials (such as SFAF, BFS2A, BFS3A, etc.), furan materials (such as DFBDDbA, BDFPDDbA, BDFPDDcA, etc.) or pyrazole compounds, but are not limited thereto. More preferably, the first electron blocking layer 220 and the second electron blocking layer 420 can be made of at least one of the compounds HT-1 to HT-62. The film thickness of the first electron blocking layer 220 and the second electron blocking layer 420 is not particularly limited, and is preferably 5nm to 15nm.

[0072] Specifically, the main function of the first light-emitting layer 230 and the second light-emitting layer 430 is to generate excitons by recombining holes and electrons injected into the first light-emitting layer 230 and the second light-emitting layer 430, and the excitons complete the electro-optical conversion process by radiation transition. The film thickness of the first light-emitting layer 230 and the second light-emitting layer 430 is not particularly limited, and is preferably 10nm to 100nm.

[0073] Furthermore, the raw materials for preparing the first light-emitting layer 230 and the second light-emitting layer 430 are a combination of the first compound and the second compound, or a combination of the first compound, the second compound and the third compound.

[0074] The first compound is a luminescent material that produces a radiation transition. According to the luminescence mechanism, the first compound can be selected from fluorescent materials, phosphorescent materials, thermally activated delayed fluorescent materials, etc., preferably phosphorescent materials containing coordination metals such as iridium and platinum, thermally activated delayed fluorescent materials containing boron nitrogen derivatives, boron oxygen derivatives, indole and carbazole derivatives, boron fluorine derivatives, and one or more fluorescent materials containing fluoranthene derivatives, pyrene derivatives, and imidazole derivatives. The second compound is a sensitizer, which acts to provide single and triplet exciton energy for the luminescent material of the first compound, preferably one or more thermally activated delayed fluorescent materials containing benzonitrile derivatives, triazine derivatives, pyrimidine derivatives, pyrazine derivatives, imidazole derivatives, benzothiophene oxide derivatives, phenanthroline derivatives, benzonitrile derivatives, phosphorus oxygen derivatives, or phosphorescent materials containing coordination metals such as iridium and platinum. The third compound is a host material, preferably one or more of carbazole derivatives, triazine derivatives, pyrimidine derivatives, aniline derivatives, benzothiophene derivatives, benzofuran derivatives, and fluorenyl derivatives.

[0075] Specifically, the first hole blocking layer 240 and the second hole blocking layer 440 can block the holes from the light-emitting layer from entering the electron transport layer, and confine the holes in the first light-emitting layer 230 and the second light-emitting layer 430, thereby improving the light-emitting efficiency. Specifically, the first hole blocking layer 240 and the second hole blocking layer 440 can be made of an electron transport material, and the electron transport material includes an aromatic heterocyclic compound containing one or more heteroatoms, preferably a nitrogen-containing ring derivative, and the nitrogen-containing ring derivative is selected from one or more of an aromatic ring containing a nitrogen six-membered ring skeleton, an aromatic ring containing a nitrogen five-membered ring skeleton, a nitrogen six-membered ring condensed aromatic ring compound, and a nitrogen five-membered ring skeleton condensed aromatic ring compound. Exemplarily, the electron transport material includes but is not limited to compounds HB-1 to HB-12, but is not limited thereto. The film thickness of the first hole blocking layer 240 and the second hole blocking layer 440 is not particularly limited, and is preferably 5nm to 15nm.

[0076]

[0077] Specifically, the first electron transport layer 250 and the second electron transport layer 450 can better transport electrons from the cathode to the first light-emitting layer 230 and the second light-emitting layer 430, thereby improving the luminous efficiency. Both the first electron transport layer 250 and the second electron transport layer 450 can be a single-layer structure or a stacked structure. The raw materials for preparing the first electron transport layer 250 and the second electron transport layer 450 include electron transport materials, and the electron transport materials include aromatic heterocyclic compounds containing one or more heteroatoms, preferably nitrogen-containing ring derivatives, and the nitrogen-containing ring derivatives are selected from the aromatic ring of a nitrogen-containing six-membered ring skeleton, an aromatic ring of a nitrogen-containing five-membered ring skeleton, a nitrogen-containing six-membered ring condensed aromatic ring compound, and a nitrogen-containing five-membered ring skeleton. One or more of the condensed aromatic ring compounds.

[0078] Illustratively, the electron transport materials in the first electron transport layer 250 and the second electron transport layer 450 include but are not limited to the following compounds ET-1 to ET-42. The electron transport materials in the first electron transport layer 250 and the second electron transport layer 450 may be the same substance or different substances.

[0079] Specifically, the thickness of the first electron transport layer 250 and the second electron transport layer 450 is not particularly limited, but is preferably 15 nm to 50 nm.

[0080]

[0081]

[0082]

[0083] Specifically, the electron injection layer 700 contacts the cathode layer 500, which can promote the injection of electrons from the cathode layer 500 into the second electron transport layer 450. The film thickness of the electron injection layer 700 is not particularly limited, and is preferably 0.5 nm to 10 nm. Further, the material of the electron injection layer 700 includes an electron injection material. Furthermore, the material of the electron injection layer 700 also includes an n-type dopant material or a metal.

[0084] Preferably, the main function of the anode layer 100 is to inject holes into the hole transport layer or the light-emitting layer. In order to obtain higher luminous efficiency and brightness of the stacked organic electroluminescent device, the light transmittance of the visible area of ​​the anode layer 100 is greater than 80%, and the square resistance is preferably less than 500Ω / cm. The raw material for preparing the anode layer 100 is preferably an anode layer 100 material with a work function of more than 4.5eV. The anode layer 100 material can be listed as indium tin oxide alloy (ITO), tin oxide (NESA), indium gallium zinc oxide (IGZO), silver, etc. Further, the anode layer 100 can be formed by thermal evaporation, sputtering, etc., and the film thickness of the anode layer 100 is 10nm to 200nm.

[0085] Preferably, the main function of the cathode layer 500 is to provide electrons to the light-emitting power source. The cathode material of the cathode layer 500 is not particularly limited. In order to improve the efficiency of electron injection and extraction, the material of the cathode layer 500 is preferably a material with a small work function, which can be aluminum, magnesium, silver, magnesium-silver alloy, magnesium-aluminum alloy, aluminum-lithium alloy, etc.

[0086] Furthermore, the cathode layer 500 can be formed by thermal evaporation, sputtering, etc., and the film thickness of the cathode layer 500 is preferably 10 nm to 200 nm. In addition, it is understood that the light emission can also be extracted from the cathode side as needed.

[0087] Correspondingly, the present invention also provides an application of a stacked organic electroluminescent device, wherein the stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.

[0088] It should be noted that the present invention has no particular limitation on the sources of the raw materials used in the following examples, and the raw materials can be commercially available products or prepared by methods well known to those skilled in the art.

[0089] The present invention will be further described below with specific embodiments:

[0090] Example

[0091] This embodiment provides a stacked organic electroluminescent device, comprising: an anode layer, a hole injection layer, a first light-emitting unit, a first connection layer, a second connection layer, a second light-emitting unit, an electron injection layer and a cathode layer arranged in sequence from bottom to top;

[0092] The first light-emitting unit includes a first hole transport layer, a first electron blocking layer, a first light-emitting layer, a first hole blocking layer and a first electron transport layer arranged in sequence from bottom to top;

[0093] The second light-emitting unit includes a second hole transport layer, a second electron blocking layer, a second light-emitting layer, a hole blocking layer, and a second electron blocking layer which are sequentially stacked from bottom to top.

[0094] Its preparation method is:

[0095] (1) A 30 mm × 30 mm × 0.7 mm glass substrate with an ITO transparent electrode was selected as the anode layer, wherein the thickness of the ITO film was set to 95 nm, and the glass substrate was ultrasonically cleaned in acetone, washing liquid, ultrapure water, and isopropanol for 10 minutes each, wherein the water was changed 3 times during the ultrapure water cleaning, and then the cleaned glass substrate was placed in an oven at 120° C. and baked for 3 hours;

[0096] (2) performing a vacuum plasma cleaning treatment on the baked glass substrate for 10 minutes;

[0097] (3) mounting the above-mentioned glass substrate after the plasma treatment on a substrate frame of a vacuum evaporation device, and firstly co-evaporating the compound HI-7 and the compound HT-10 on the side where the transparent electrode line is formed so as to cover the transparent electrode, wherein the concentration of the compound HI-7 is set to 3 wt %, to form a hole injection layer with a film thickness of 10 nm;

[0098] (4) evaporating compound HT-10 on the hole injection layer to form a first hole transport layer with a thickness of 40 nm;

[0099] (5) evaporating compound HT-48 on the first hole transport layer to form a first electron blocking layer with a film thickness of 10 nm;

[0100] (6) A third compound combination GH and a first compound GD are co-evaporated on the first electron blocking layer to form a first light-emitting layer with a thickness of 40 nm. The concentration of the first compound GD in the first light-emitting layer is set to 4 wt %. The structures of the third compound combination GH and the first compound GD used are shown below:

[0101]

[0102] (7) vapor depositing a layer of HB-11 on the first light-emitting layer to form a first hole blocking layer with a thickness of 10 nm;

[0103] (8) evaporating ET-9 on the first hole blocking layer to form a first electron transport layer with a thickness of 40 nm;

[0104] (9) vapor-depositing an n-type dopant material and an organic electron transport material on the first electron transport layer to form a first connecting layer, wherein the doping concentration of the n-type dopant material decreases from one side of the second connecting layer to the side of the first light-emitting layer; the n-type dopant material, the organic electron transport material, the film thickness, and the doping concentration of the n-type dopant material used are specifically set as shown in Table 1 below;

[0105] (10) Co-evaporating the compound HI-7 and the compound HT-10 on the first connecting layer to form a second connecting layer with a thickness of 50 nm, wherein the concentration of the compound HI-7 in the second connecting layer is set to 3 wt %;

[0106] (11) evaporating compound HT-10 on the second connecting layer to form a second hole transport layer with a thickness of 50 nm;

[0107] (12) evaporating compound HT-48 on the second hole transport layer to form a second electron blocking layer with a film thickness of 10 nm;

[0108] (13) The third compound combination GH and the first compound GD were co-evaporated on the fourth hole transport layer to form a second light-emitting layer with a thickness of 40 nm. The concentration of the first compound GD in the second light-emitting layer was set to 5 wt %;

[0109] (14) vapor depositing a layer of HB-11 on the second light-emitting layer to form a second hole blocking layer with a thickness of 10 nm;

[0110] (15) evaporating ET-9 on the second hole blocking layer to form a second electron transport layer with a thickness of 30 nm;

[0111] (16) Liq is evaporated on the second electron transport layer to form an electron injection layer with a thickness of 2 nm. The structure of the Liq used is as follows:

[0112]

[0113] (17) Metal Al was evaporated on the electron injection layer to form a cathode layer with a film thickness of 100 nm.

[0114] The compound combinations of the first connection layer formed in Examples 1 to 12 are shown in Table 1 below.

[0115] Table 1 Process parameters for forming the first connection layer in Examples 1 to 7

[0116]

[0117]

[0118] Comparative Example 1

[0119] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 1, except that the doping concentration of the n-type dopant material in the first connecting layer is 1 wt %, and the doping concentration does not vary with the thickness of the first connecting layer.

[0120] Comparative Example 2

[0121] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 1, except that the doping concentration of the n-type dopant material in the first connecting layer increases linearly from 1 wt % near the second connecting layer to 12 wt % near the first light-emitting layer.

[0122] Comparative Example 3

[0123] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 1, except that the doping concentration of the n-type dopant material in the first connecting layer is 12 wt %, and the doping concentration does not vary with the thickness of the first connecting layer.

[0124] Comparative Example 4

[0125] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 6, except that the doping concentration of the n-type dopant material in the first connecting layer is 1 wt %, and the doping concentration does not vary with the thickness of the first connecting layer.

[0126] Comparative Example 5

[0127] This comparative example provides a stacked organic electroluminescent device, which is basically the same as Example 6, except that the doping concentration of the n-type dopant material in the first connecting layer is 5 wt %, and the doping concentration does not vary with the thickness of the first connecting layer.

[0128] Performance Testing

[0129] The stacked organic electroluminescent devices prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were measured using a spectroradiometer CS-2000 (Konica Minolta) and a digital source meter 2420 (Keithley) at 3000 cd / m 2 Driving voltage, external quantum efficiency (EQE), EQE efficiency roll-off and CIE1931 chromaticity coordinates (x, y) at brightness; measured using device lifetime test at a current density of 50 mA / cm 2 When the prepared organic electroluminescent device is driven, the device brightness decays to a lifetime (T95) of 95% of the initial brightness; the performance evaluation results are shown in Table 2 below.

[0130] Table 2 Performance evaluation results of examples and comparative examples

[0131]

[0132] From the above results, it can be seen that the doping concentration reduction process of the n-type dopant material introduced into the first connection layer can not only reduce the driving voltage of the stacked device and improve the life of the device to a certain extent, but also avoid the annihilation effect of the device luminous efficiency caused by the higher n-type dopant concentration. On the one hand, setting a higher n-type dopant concentration at the interface between the first and second connection layers can eliminate the energy level mismatch problem between the first connection layer and the second connection layer, so that the carriers generated in the connection layer can be smoothly injected into the light-emitting layer, and avoid the problem of obvious voltage drop at the connection layer. On the other hand, setting a lower n-type dopant concentration at the contact interface between the first connection layer and the light-emitting unit can avoid the luminescence quenching effect of the n-dopant, and its LUMO energy level matches the LUMO energy level of the electron transport layer, but obtains a better electron injection effect, so the driving voltage of the device is lower.

[0133] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A stacked organic electroluminescent device, characterized in that: include: An anode layer, at least two light-emitting units, a cathode layer, and a connection layer for connecting two adjacent light-emitting units are sequentially arranged from bottom to top; the connection layer includes a first connection layer and a second connection layer sequentially arranged from bottom to top; The first connection layer is made of an n-type dopant material and an organic electron transport material, and the doping concentration of the n-type dopant material of the first connection layer gradually decreases from the second connection layer side to the light-emitting unit side; The second connection layer is composed of a p-type dopant material and an organic hole transport material.

2. The stacked organic electroluminescent device according to claim 1, characterized in that: The doping concentration of the n-type dopant material of the first connection layer decreases in a linear decreasing manner from the second connection layer side to the light emitting unit side.

3. The stacked organic electroluminescent device according to claim 1 or 2, characterized in that: The doping concentration of the n-type dopant material on the side of the first connection layer close to the second connection layer is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connection layer close to the light emitting unit is in the range of 0.5 mass % to 5 mass %.

4. The stacked organic electroluminescent device according to claim 1, characterized in that: The doping concentration of the n-type dopant material of the first connection layer decreases in a gradient manner from the second connection layer side to the light-emitting unit side, and the set concentration gradient number is an integer greater than or equal to 3.

5. The stacked organic electroluminescent device according to claim 1 or 4, characterized in that: The doping concentration of the n-type dopant material on the side of the first connection layer close to the second connection layer is in the range of 5 mass % to 15 mass %, and the doping concentration of the n-type dopant material on the side of the first connection layer close to the light emitting unit is in the range of 0.5 mass % to 5 mass %.

6. The stacked organic electroluminescent device according to claim 1, characterized in that: The thickness of the first connecting layer is 20nm to 100nm; The thickness of the second connection layer is 20 nm to 300 nm.

7. The stacked organic electroluminescent device according to claim 1, characterized in that: The n-type dopant material is selected from at least one of lithium, cesium, magnesium, gold, silver, copper, zinc, ytterbium, molybdenum trioxide, cesium carbonate, and lithium carbonate.

8. The stacked organic electroluminescent device according to claim 1, characterized in that: The organic electron transport materials are all composed of nitrogen heterocyclic units, and the nitrogen heterocyclic units are selected from at least one of compounds N-1 to compounds N-28:

9. The stacked organic electroluminescent device according to claim 1, characterized in that: The p-type dopant material of the second connecting layer is a deep LUMO energy level material, and the deep LUMO energy level material is selected from at least one of MoO3, WO3, V2O5, MoO2, Co3O4 and the following compounds HI-1 to HI-18:

10. An application of the stacked organic electroluminescent device according to any one of claims 1 to 9, characterized in that: The stacked organic electroluminescent device is used to prepare an organic electroluminescent display or an organic electroluminescent lighting device.

Citation Information

Patent Citations

  • Series organic light-emitting device

    CN114520301A

  • Laminated organic light-emitting device and application thereof

    CN116583133A

Cited By

  • Laminated organic light-emitting device and application thereof

    CN121078902A